معالم لقراءة المعهود الفقهي في ميزان مقاصد الأحكام - لشهب، أبو بكر (جامعة الشهيد حمه لخضر الوادي, 2014)
Parameters for Interpreting the Conventional Jurisprudence in the Scale of provisions’ intentions Descendants' (followers') interpretations of what was written or left by their predecessors requires some parameters imposed by changes and differences in time, space and circumstances, which save the jurisprudent heritage, its stature, and the continuity of religious law (Sharia). What is worth mentioning here is the type of interest or profit of juridical provisions, according to both traditional and modern juristic scholars, is of great significance. Additionally, considering the objectives and consequences, and the compliance with the integral meaning of texts requires equilibrium and asymptotical approaching. Moreover, the interpretation of texts should not ignore the time and the circumstances that we live in; this is because interest (profit) and jurisprudence can be interchangeable. Now, in order to attain a fruitful and profitable interpretation of religious texts, and the conventional jurisprudence involved and renewable, but constrained by the same rules, we need to set equilibrium between literal and pragmatic meaning of texts, and between judicial discretion and changes in time and space. This is because inflexibility towards what was handed down to us is not desirable; at the same time, the failure to restrain judicial discretion is unconvinced. This is, of course, what this research intends to achieve
إن قراءة الخلف لما تركه السلف تحتاج إلى معالم يفرضها تغير الزمان واختلاف المكان وتبدل الأحوال، معالم تحفظ للموروث الفقهي مكانته ولمؤلفيه قدرهم، وللشريعة استمرارها؛ ذلك أن جنس المصلحة معتبر في عموم الأحكام الشرعية عند أئمة الفقه وأصوله قديما وحديثا، ومراعاة المقاصد والمالات مع التزام ظواهر النصوص يحتاج إلى موازنة ومقاربة. كما أن إهمال الواقع الذي يعيشه الناس مكابرة، والمصلحة شريعة والشريعة مصلحة، وحتى تكون قراءة النص الشرعي مثمرة ونافعة، والمعهود الفقهي القديم مفعل ومتجدد، ثم يضبط الحديث منه بالضوابط والقواعد ذاتها، لابد من موازنة بين منطوق النص ومدلوله، وبين الاجتهاد الفقهي وتغير الزمان والأحوال، إذ الجمود على المنقولات معيب، وعدم ضبط الاجتهاد مريب.
Keywords: الأحكام الفقهية -- مقاصد الأحكام -- المعهود الفقهي -- الاجتهاد -- النصوص الشرعية